Contractility and kinetics of human fetal and human adult skeletal muscle. (14th June 2013) - Racca, Alice W.; Beck, Anita E.; Rao, Vijay S.; Flint, Galina V.; Lundy, Scott D.; Born, Donald E.; Bamshad, Michael J.; Regnier, Michael
Key points The contractile properties of human fetal skeletal muscle are unknown. Reductionist approaches such as isolated myofibril and isolated contractile protein biomechanical assays allow study of activation and relaxation properties of skeletal muscle from different sources. We have tested the contractile properties of human fetal skeletal myofibrils and myosin in comparison with myosin and myofibrils from human adult skeletal muscle and rabbit psoas muscle. Human fetal skeletal myofibrils have much slower kinetics of activation and relaxation compared to myofibrils from adult human or rabbit psoas skeletal muscle. Investigations using altered substrate and product conditions for both the in vitro motility assay and myofibril mechanics/kinetics indicate that fetal muscle acto‐myosin crossbridges cycle more slowly than, but with similar rate‐limiting steps to, the adult myosin isoforms. Abstract Little is known about the contraction and relaxation properties of fetal skeletal muscle, and measurements thus far have been made with non‐human mammalian muscle. Data on human fetal skeletal muscle contraction are lacking, and there are no published reports on the kinetics of either fetal or adult human skeletal muscle myofibrils. Understanding the contractile properties of human fetal muscle would be valuable in understanding muscle development and a variety of muscle diseases that are associated with mutations in fetal muscle sarcomere proteins. Therefore, we characterised the contractile properties of developing human fetal skeletal muscle and compared them to adult human skeletal muscle and rabbit psoas muscle. Electron micrographs showed human fetal muscle sarcomeres are not fully formed but myofibril formation is visible. Isolated myofibril mechanical measurements revealed much lower specific force, and slower rates of isometric force development, slow phase relaxation, and fast phase relaxation in human fetal when compared to human adult skeletal muscle. The duration of slow phase relaxation was also significantly longer compared to both adult groups, but was similarly affected by elevated ADP. F‐actin sliding on human fetal skeletal myosin coated surfaces in in vitro motility (IVM) assays was much slower compared with adult rabbit skeletal myosin, though the Km(app) (apparent (fitted) Michaelis–Menten constant) of F‐actin speed with ATP titration suggests a greater affinity of human fetal myosin for nucleotide binding. Replacing ATP with 2 deoxy‐ATP (dATP) increased F‐actin speed for both groups by a similar amount. Titrations of ADP into IVM assays produced a similar inhibitory affect for both groups, suggesting ADP binding may be similar, at least under low load. Together, our results suggest slower but similar mechanisms of myosin chemomechanical transduction for human fetal muscle that may also be limited by immature myofilament structure.